2015
DOI: 10.4040/jkan.2015.45.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Self-determination Theory based a Motivational Interviewing YOU-TURN Program for Smoking Cessation among Adolescents

Abstract: Purpose: In this study, the effectiveness of a motivational interviewing smoking cessation YOU-TURN program for adolescents was examined. The program was based on the self-determination theory. Methods: The study was carried out with a nonequivalent control group pretest-posttest design. Participants in the present study were 136 high school students living in D city. The students were assigned to the experimental group (n=52) who participated in the motivational interviewing smoking cessation YOU-TURN program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
2
1
0
1
Order By: Relevance
“…At the end of the smoking cessation programs, the mean difference of self-esteem in the intervention group was significantly higher than that of the control group, which is correlated with many studies including that of Kim[13], who studies the effects of a self-esteem and smoking cessation self-efficiency improvement program on smoking high school students in a quasi-experimental study. The study is also consistent with Ha and Choi’s quasi-experimental study[22] researching the effectiveness of the self-determination theory based on a motivational interviewing program called YOU-TURN for smoking cessation among adolescents, and Kim[23], who studies the effects of a self-esteem and smoking cessation self-efficiency improvement program on high school students who smoke. Due to the variety of activities, students can develop their self-esteem and are encouraged to identify their aptitude for various activities.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…At the end of the smoking cessation programs, the mean difference of self-esteem in the intervention group was significantly higher than that of the control group, which is correlated with many studies including that of Kim[13], who studies the effects of a self-esteem and smoking cessation self-efficiency improvement program on smoking high school students in a quasi-experimental study. The study is also consistent with Ha and Choi’s quasi-experimental study[22] researching the effectiveness of the self-determination theory based on a motivational interviewing program called YOU-TURN for smoking cessation among adolescents, and Kim[23], who studies the effects of a self-esteem and smoking cessation self-efficiency improvement program on high school students who smoke. Due to the variety of activities, students can develop their self-esteem and are encouraged to identify their aptitude for various activities.…”
Section: Discussionsupporting
confidence: 83%
“…The cigarette intake per day average was assessed, and by the end of the 24th week, there were six smokers (17.10 percent) in the control group (2.90 percent), a result that is similar to other studies [13,22,29]. The average number of cigarettes per day in the intervention group might have decreased because this study aimed to modify internal behaviors, like self-esteem, attitude toward smoking and perceived control over smoking.…”
Section: Discussionsupporting
confidence: 76%
“…, 스트레스 [1,6,7], 대학생활적응의 어려움 [7,8] [21,22], 수 용전념치료 [23], 집단상담 [24], 스마트폰 및 어플리케이션 활용 [6,25] [26,27], 체중감소 [28], 중학생 대상 금연 [29], 고등학생 대상 인터넷 중독 집단상담 프로그 램 [30]…”
unclassified
“…Such interventions have been used in other contexts as well. An anti-smoking study conducted by Ha and Choi [60] showed that a program based on the degenerative facts related to smoking, such as health-related issues, improved the psychological needs of individuals to reduce smoking, leading to intrinsic motivation. Moreover, anti-smoking apps have been identified as improving intrinsic motivation by presenting intrinsic goal content (health-related information) and extrinsic motivations by presenting extrinsic goal content (money-related information) [61].…”
Section: Self-determination Theorymentioning
confidence: 99%